2018 Physics Education Research Conference Proceedings 2019
DOI: 10.1119/perc.2018.pr.stein
|View full text |Cite
|
Sign up to set email alerts
|

Confirming what we know: Understanding questionable research practices in intro physics labs

Abstract: Many institutions are changing the focus of their introductory physics labs from verifying physics content towards teaching students about the skills and nature of science. As instruction shifts, so too will the ways students approach and behave in the labs. In this study, we evaluated students' lab notes from an early activity in an experimentation-focused lab course. We found that about 30% of student groups (out of 107 groups at three institutions) recorded questionable research practices in their lab notes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…In verification labs, where the goal was to obtain an outcome to verify a particular result, students in the intervention condition recorded fewer agency-based decisions than in evaluation labs, where the goal was to evaluate a model or compare multiple possible models. Previous research has suggested that when students know the intended result of the experiment, they may feel encouraged to "massage their data" [23] or engage in questionable research practices to get the expected outcome [57][58][59]. Evaluation labs (at least for the intervention condition) encouraged revision and exploration, likely because there was no clear end point to pursue [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In verification labs, where the goal was to obtain an outcome to verify a particular result, students in the intervention condition recorded fewer agency-based decisions than in evaluation labs, where the goal was to evaluate a model or compare multiple possible models. Previous research has suggested that when students know the intended result of the experiment, they may feel encouraged to "massage their data" [23] or engage in questionable research practices to get the expected outcome [57][58][59]. Evaluation labs (at least for the intervention condition) encouraged revision and exploration, likely because there was no clear end point to pursue [66].…”
Section: Discussionmentioning
confidence: 99%
“…[56]. We used the two common evaluation labs to evaluate the quality of students' decision making because we expected that the coordination of theory and evidence in verification labs would be impeded by potential confirmation biases or orientations [57][58][59]. Lab D may be classified as better affording epistemic agency than lab E, because there is an intuitive expectation for the result in lab E (that the collision with the ground would result in more energy loss than drag).…”
Section: Identifying Decision Making Qualitymentioning
confidence: 99%
“…Recent studies suggest that students in traditional laboratories (i.e., those that use confirmatory exercises) tend to engage in questionable research practices when their results deviate from the expected results (Stein et al, 2018;Smith et al, 2020).…”
Section: Theme: Decrease In Unethical Behavior Number Of Responses (%): 4 (31%)mentioning
confidence: 99%
“…Students may feel empowered to express themselves more authentically in learning experiences and seek out alternative ideas and methods from their peers. Students may more readily bring up limitations and biases that will support their future investigative and practical choices in labs and research and in other sciences [22]. Students may also reference examples of subjectivity such as structural bias and barriers when they discuss their career choices.…”
Section: Human Values Introduces Subjectivitymentioning
confidence: 99%